2018
DOI: 10.1016/j.aninu.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Changing dietary n-6:n-3 ratio using different oil sources affects performance, behavior, cytokines mRNA expression and meat fatty acid profile of broiler chickens

Abstract: Typical formulated broiler diets are deficient in n-3 poly-unsaturated fatty acids (PUFA) due to widening n-6:n-3 PUFA ratio which could greatly affect performance, immune system of birds and, more importantly, meat quality. This study was conducted to evaluate the effect of modifying dietary n-6:n-3 PUFA ratio from plant and animal oil sources on performance, behavior, cytokine mRNA expression, antioxidative status and meat fatty acid profile of broiler chickens. Birds (n = 420) were fed 7 diets enriched with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…Interestingly, low levels of dietary FO (such as 2%) have been demonstrated as being more effective than high levels of FO on improving performance [16]. The improved performance by dietary n-3 PUFA supplementation in broilers is also due to the narrowing dietary n-6/n-3 PUFA ratio (close to 4:1 or 2.5:1) and increasing the n-3 PUFA level that could effectively improve immune responses [17]. Moreover, high levels of n-3 PUFA can improve immunity and anti-inflammatory functions by decreasing the contents of inflammatory biomarkers, consequently leading to better performance in broilers [18].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, low levels of dietary FO (such as 2%) have been demonstrated as being more effective than high levels of FO on improving performance [16]. The improved performance by dietary n-3 PUFA supplementation in broilers is also due to the narrowing dietary n-6/n-3 PUFA ratio (close to 4:1 or 2.5:1) and increasing the n-3 PUFA level that could effectively improve immune responses [17]. Moreover, high levels of n-3 PUFA can improve immunity and anti-inflammatory functions by decreasing the contents of inflammatory biomarkers, consequently leading to better performance in broilers [18].…”
Section: Discussionmentioning
confidence: 99%
“…The result of this present study agreement with several previous study. In poultry, the consumption of diets high in PUFA, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), it has been demonstrated to improve body weight gain (27,28). The enrichment n-3 PUFA containing fish oil at 2% and 4% in broiler diets showed increased accumulation of n-3 LC-PUFA in muscle and adipose tissues (27).…”
Section: Effect Of Cfo and L Casei Wb 315 On Levels Of Feed Intake mentioning
confidence: 99%
“…In poultry, the consumption of diets high in PUFA, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), it has been demonstrated to improve body weight gain (27,28). The enrichment n-3 PUFA containing fish oil at 2% and 4% in broiler diets showed increased accumulation of n-3 LC-PUFA in muscle and adipose tissues (27). The results of another study showed that EPA, DHA and docosapentaenoic acid (DPA) and total n-3 PUFA were significantly increased in 2% SALmate-and 5% of salted chickens compared with control and ZnB were obtained (p<0.05) (29).…”
Section: Effect Of Cfo and L Casei Wb 315 On Levels Of Feed Intake mentioning
confidence: 99%
“…Average live body weight of ducks was measured at the end of starter and finisher periods and feed intake was recoded at the end of the two rearing periods. And, accordingly, growth performance parameters, as body weight gain, feed:gain ratio and protein efficiency ratio were calculated as we previously reported (Ibrahim et al 2018).…”
Section: Growth Performance Measurementsmentioning
confidence: 99%